1990
DOI: 10.1161/01.str.21.9.1299
|View full text |Cite
|
Sign up to set email alerts
|

Arterial pathology in cerebellar infarction.

Abstract: We reviewed 88 pathologically proven cerebellar infarcts, examining the entire thoracocervical arterial system (including the spinal part of the vertebral artery, the intracranial arteries, and the heart) in all cases. For 50 infarcts, we found an arterial occlusion. The intracranial part of the vertebral artery was involved in 38 infarcts (76%), the basilar artery in 20 infarcts (40%), and a cerebellar artery in 12 infarcts (24%). Eight infarcts were due to bilateral distal vertebral artery occlusions. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 34 publications
1
36
0
4
Order By: Relevance
“…Our cases involved large infarcts in regions of Ͼ1 cerebellar vessel, in contrast to the vast majority of cerebellar strokes, which are typically in the distribution of a single vessel. 16,17 The neuropharmacologic literature regarding THC generally describes neuroprotective effects from oxidant injury at least in tissue culture 18,19 as well as therapeutic effects including analgesia, ocular hypotension, and antiemesis. 18 In a rat model of focal cerebral ischemia, synthetic cannabinoid agonists have been reported to reduce infarct volume.…”
Section: Discussionmentioning
confidence: 99%
“…Our cases involved large infarcts in regions of Ͼ1 cerebellar vessel, in contrast to the vast majority of cerebellar strokes, which are typically in the distribution of a single vessel. 16,17 The neuropharmacologic literature regarding THC generally describes neuroprotective effects from oxidant injury at least in tissue culture 18,19 as well as therapeutic effects including analgesia, ocular hypotension, and antiemesis. 18 In a rat model of focal cerebral ischemia, synthetic cannabinoid agonists have been reported to reduce infarct volume.…”
Section: Discussionmentioning
confidence: 99%
“…Top-of-the-BA occlusions are mainly of embolic origin and, therefore, thrombolytic therapy is more effective than in occlusions representing the end point of a protracted artherosclerotic disease. In addition, the thrombolytic mass is smaller than with other types of occlusion [14, 15]. Moreover, the branches penetrating into the brain stem may stay occluded in patients with caudal, midbasilar and mixed-type occlusions even after adequate recanalization of the BA, the mechanisms being the same as those described in striatocapsular infarcts after middle cerebral artery occlusions and recanalization [16].…”
Section: Discussionmentioning
confidence: 99%
“…Past reports link ICVA disease inextricably with in farction in the proximal posterior circulation territory which include the medulla [6][7][8][9] and the PICA cerebellum [10][11][12][13][14]21. 22], However, in our series of patients with ICVA disease, only one-fourth had infarcts limited to the proximal intracranial territory'.…”
Section: Locations O F Posterior Circulation Ischemiamentioning
confidence: 70%
“…In another necropsy study of 6 patients with fatal ICVA disease the location of the infarcts was mainly hemimedullary and lower pons [4], ICVA occlusion was the most common vascular lesion found in necropsy studies of patients with lateral medulla ry infarcts [6][7][8][9] and the portion of the cerebellum sup plied by the posterior inferior cerebellar arteries [10][11][12][13][14], A few clinical studies have been reported [15][16][17][18][19] but the numbers of patients were small, and the studies were ret rospective and anecdotal. Bilateral ICVA disease was dis cussed only in several retrospective studies [18,19].…”
Section: Introductionmentioning
confidence: 99%